Local feminist perspectives as transformative levers: Women's health and climate action in India - Sreerupa Sengupta; Divya Singhal; Ananya Chakraborty (German Institute of Development and Sustainability (IDOS), 2025)
This study explores the transformative potential of local feminist perspectives in addressing systemic gender inequalities in India, focusing on women's health and climate action. Anchored in global frameworks, such as the Beijing Declaration (1995) and the Sustainable Development Goals (SDGs), and rooted in India's historical milestones, such as the Towards Equality Report in 1974 (Government of India, 1974), this research examines how caste, class, gender, sexuality and disability intersect to perpetuate inequities. Despite progress in education, health, and political representation, deep-seated patriarchal norms and structural barriers continue to undermine women's agency, as reflected in India's low ranking on the Global Gender Gap Report 2024 (World Economic Forum, 2024). Using intersectional and eco-feminist frameworks, the study employs a qualitative, multi-method approach, including 31 key informant interviews and a stakeholder dialogue involving 40 participants from non-governmental organisations (NGOs), community organisations and feminist collectives. By integrating lived experiences with policy analysis, this study highlights how local feminist movements in India have challenged entrenched social norms, amplified marginalised voices and innovated to provide context-specific solutions. The findings reveal persistent health inequities among women, compounded by caste and disability, and critique health policies for their technocratic focus. Interventions by community organisations as well as governments, such as community health workers and self-help groups, have emerged as vital platforms for addressing reproductive and menstrual health needs while fostering social change. In climate action, women face disproportionate vulnerabilities due to caregiving roles and resource dependencies. However, localised initiatives, including women-led renewable energy programmes and sustainable agriculture practices, showcase their potential as agents of environmental resilience. The study advocates for recognising intersectional vulnerabilities, converging across sectors, improving participatory governance, strengthening capacity building of community organisations, and including divergent experiences of women in policy and intersectional funding models. By situating feminist knowledge within actionable frameworks, it presents a replicable model for integrating gender justice into health and climate strategies, offering lessons for global contexts. The report underscores the necessity of sustained collaboration among community actors, women's advocacy groups, policymakers and donors to foster systemic equity and resilience.
Keywords: 320; Gender; India; Feminism